Frequency of Temporomandibular Joint Dysfunction among Undergraduate University Students: A Cross Sectional Study: Frequency of Temporomandibular Joint Dysfunction - Ilyas, Tamknat; Wadood, Asma; Jawa, Rabia; Ali, Sidra; Ayub, Rahat; Maqbool, Sania; Qamar, Saddiqa (Pakistan Journal of Health Sciences, 2023)
Temporomandibular joint dysfunction (TMJD) is an umbrella term covering pain and dysfunction of the muscles of mastication (jaw muscles). Disorder of temporomandibular Joint is one of the most common health problems. It is a term used to cover a number of multiple clinical issues related to temporomandibular joint, muscles of mastication and teeth. The trio that effects the arrangement and balance of TMJ, dental occlusion and muscles of mastication revolves mainly around “psychological, postural and structural elements. Objective: To find out Frequency of TMJD among undergraduate university students. Methods: Cross-sectional survey was conducted in duration of 3 months after approval of synopsis across University of Management and Technology (UMT). Self-designed questionnaire and TMJ dysfunction questionnaire was used. The sample size of this study was 200 calculated by Rao software. It took 9 months’ time period to complete the study. Random sampling technique has been used in this study to collect the data. SPSS version 21 was used to analyze data, frequency tables and bar charts were made. Results: Results showed that 63.5% (n=127) were considered themselves chronically fatigued and 77% (n=154) grinded their teeth at night. 64% (n=128) of the students were from health sciences background. This shows the association of prevalence of TMJDs and stress in university students. Conclusions: Study showed high frequency of TMD amongst students due to chronic fatigue, overload of study, poor ergonomics, and working hours, which are associating risk factors for TMD. Stress management & good ergonomics strategies are required.